Seismic Response Analysis of a Curved Bridge under Near-Fault and Far-Field Ground Motions - Peng Su; Xiaoyi Zhu; Yanjiang Chen; Bing Xue; Bing Zhang (Applied Sciences, 2022)
To study the influence of near-fault and far-field (FF) ground motions on a curved girder bridge, a 1:10 scale curved bridge shaking table test model was constructed. Three types of ground motions, namely, near-fault pulse (NP), near-fault non-pulse (NN), and FF ground motions, were selected and employed in the test model. The test results indicated that the seismic response of the curved bridge in the excitation of NP ground motion is significantly higher than that in the excitation of NN and FF ground motions, and is destructive to the curved bridge. The displacement of the curved bridge has spatial characteristics in the excitation of NP ground motions. The rotation generated by the curved bridge is easy to cause bearing shedding or girder falling at the low pier. The amplification of pier height increases the displacement response at the high pier.